Tourism in São Tomé and Principe: the forgotten pearl - Loureiro, S. M. C.; Ferreira, E. S. (Revista Turismo e Desenvolvimento/Journal of Tourism and Development, 2014)
São Tomé and Príncipe is a small African country, which has been facing several vulnerabilities and constraints that have been limiting its development process since its independence. Hence, it is vital to improve alternative ways of development, in order to overcome this disadvantage. This article analyses São Tomé and Príncipe tourism destination competitiveness based on 27 interviews conducted in São Tomé and Príncipe. The conclusions show that the main qualify determinants are: the natural resources, the unique landscape, the cocoa and coffee plantations, the friendly locals and the peace and safety. But, on the other hand, this country reveals a competitive weakness, mainly due to the lack of infrastructures, technical training for hospitality and tourism, coordination among ministries, inter-relationship among public, private and non-profit organizations, as well as external marketing communication.